Economically optimal water depth and grain yield of common bean subjected to different irrigation depths - Chaiane G. da Conceição; Adroaldo D. Robaina; Marcia X. Peiter; Ana R. C. Parizi; João A. da Conceição; Jhosefe Bruning (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Common bean crop plays an important role in the world, not only in economic aspects but also in social development. The objective of this study was to evaluate the grain yield and the economically optimal water depth which reflects the maximum technical efficiency of the common bean crop. The experiment was conducted in greenhouse, in Alegrete - RS, from February to May 2016. A completely randomized design was used, consisting of five water replacement treatments (25, 50, 75, 100 and 125% crop evapotranspiration - ETc) and four replicates. Based on the obtained results, both water deficit and water excess directly affected the final grain yield of the crop. Maximum grain yield was 3,554.1 kg ha-1, obtained by applying 492.72 mm (100% ETc). On the other hand, the economically optimal water depth was estimated at 91.2% ETc, indicating that water depths above this value are not suitable for maximum technical efficiency in the common bean crop under these conditions. It was concluded that the water depth equivalent to 100% ETc maximizes grain yield for the region of Alegrete-RS, and irrigation is considered a solution in the water supply to the common bean crop during critical periods.